2019
DOI: 10.1002/dneu.22733
|View full text |Cite
|
Sign up to set email alerts
|

Early lesion of the reticular thalamic nucleus disrupts the structure and function of the mediodorsal thalamus and prefrontal cortex

Abstract: The thalamic reticular nucleus (TRN), part of the thalamus, is a thin GABAergic cell layer adjacent to the relay nuclei of the dorsal thalamus. It receives input from the cortex and other thalamic nuclei and provides major inhibitory input to each thalamic nucleus, particularly the mediodorsal nucleus (MD). As the MD is important for supporting optimal cortico-thalamo-cortical interactions during brain maturation, we hypothesized that that early damage to the TRN will cause major disturbances to the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 95 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have found a positive correlation between high thalamic activity and anxiety (Geng et al, 2018). The level of anxiety increased in rats with electrolytic lesions in the thalamic reticular nucleus (El Boukhari et al, 2019). Adult rats with bilateral medial dorsal (MD) lesions in the early postpartum period showed impairment of recognition memory and increased anxiety-like behavior (Ouhaz et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have found a positive correlation between high thalamic activity and anxiety (Geng et al, 2018). The level of anxiety increased in rats with electrolytic lesions in the thalamic reticular nucleus (El Boukhari et al, 2019). Adult rats with bilateral medial dorsal (MD) lesions in the early postpartum period showed impairment of recognition memory and increased anxiety-like behavior (Ouhaz et al, 2017).…”
Section: Discussionmentioning
confidence: 95%